ANALYSIS OF CUSTOMER SATISFACTION LEVELS USING THE CSI METHOD AND SWOT ANALYSIS - Femmy Ramadha Lumantya; Didi Samanhudi; Iriani Iriani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The increasing existence of coffee shops with various interesting concepts supported by unique beverage variations makes every coffee shop owner face tough competition. This study aims to determine the level of customer satisfaction, including marketing mix (7P) product, price, place, promotion, people, process, and physical evidence, to determine marketing strategies using the SWOT method at the XYZ coffee shop. This study uses the CSI and SWOT methods. Based on the results of CSI calculations, a satisfaction value of 72.01% is obtained; this indicates that the customer is satisfied. Whereas in the SWOT analysis, Coffee Shop XYZ occupies Quadrant I, which means the company has strengths to take advantage of and maximize existing opportunities. The strategy that the Titik Koma Tenggilis coffee shop can take is to maximize online sales and marketing by adding Tiktok as a digital marketing medium and holding a reward point program for customers with member cards